Solvent-specific, DAST-mediated intramolecular Friedel–Crafts reaction: access to dibenzoxepine-fused spirooxindoles. Issue 8 (4th February 2021) - Samikannu, Ramesh; Sethuraman, Sankaranarayanan; Akula, Nagaraja; Radhakrishnan, Vignesh; Kamisetti, Srinivasarao; Banu, Shabana; Vetrichelvan, Muthalagu; Gupta, Anuradha; Li, Jianqing; Rampulla, Richard; Mathur, Arvind
Abstract : DAST-mediated intramolecular Friedel–Crafts cyclization is developed for the synthesis of novel spirooxindoles fused with dibenzoxepine moieties. Abstract : A facile, DAST-mediated intramolecular cyclization of 3-hydroxy-3-(2-((3-methoxybenzyl)oxy)phenyl)indolin-2-one derivatives for the synthesis of spirooxindoles fused with dibenzoxepine moieties is described. The success of this reaction is highly dependent on the choice of solvent (promoted by DCM and 1, 2-DCE) and the electronic nature of the pendant aromatic ring, which is favored by the presence of electron-donating substituents. The reaction is believed to proceed through an intramolecular Friedel–Crafts-type reaction. Various dibenzoxepine-fused spirooxindoles were successfully synthesized in up to 98% yield. This methodology provides libraries of structurally diverse and medicinally important small molecules that could aid in the search for new bioactive molecules.